Legal Counseling on Salt Pond Land Certification to Avoid Land Conflicts in Pagagan Village, Pamekasan Regency - Mukhlish Mukhlish; Muwaffiq Jufri (Universitas Negeri Semarang, 2023)
The occurrence of several land ownership claims for salt ponds in several areas in Pamekasan initiated the Community Service Team to carry out legal counseling activities related to the importance of certifying ownership rights to salt pond land belonging to salt farmers in Pagagan Village, Pademawu District, Pamekasan Regency for which currently still has the status of girik land. This activity uses the method of presenting material about the urgency and benefits of land certification, as well as providing assistance to the community in the process of land certification. The results obtained in this community service activity are increasing public understanding regarding the importance of salt pond land certification. This activity provides benefits for the community to avoid ownership disputes over salt pond land.